Creating, framing, reflecting—dance as embodied reflective practice in professional development for physical education teachers - Schwender, Tina M.; Rudi, Helena; Stortz, Susanne (Frontiers in Education, 2025)
BackgroundThe ability to (self)-reflect has been described as a key competence in the teaching profession and is particularly relevant for physical education teachers as they are exposed to complex, unpredictable, and dynamic situations. As an Embodied Reflective Practice, Educational Dance can contribute to the promotion of embodied self-awareness and embodied reflexivity by consciously foregrounding its inherent reflective components. The objective of this study is to explore the relationship between embodied experience and reflection within the narratives of physical education teachers. The study addresses the following research questions: (i) How does the (self)-reflective capacity of the participating teachers manifest in the context of creative movement work? What connections between embodied experiences and potential reflections can be found in the teacher's subjective narrative constructions? (ii) What bodily-kinesthetic experiences are encountered? Which (movement-) moments or experiences stimulate reflection processes, and why?MethodsThe exploratory case study analyzes interview data from physical education teachers (N = 18), who participated in a continuing education course in dance teaching, using qualitative content analysis.FindingsThe analysis reveals two main categories, namely Moments of Embodied Reflection Processes and Teaching Design as Influential Variable on Embodied Reflective Moments. Various moments of embodied reflection processes are identified: Wellbeing/Contentment, Letting Go and Engaging, Deepened Sensory Perception, Being Impressed/Being Surprised, Connectedness with Others as well as Irritation/Resistance. A co-occurrence analysis shows that certain moments occur with specific aspects of the teaching design as influential variables for the respective aesthetic experience.DiscussionIn the exploratory and creative field of Educational Dance examined in this study, reflections are increasingly tied to an aesthetic experience, serving as a stimulus for embodied reflection processes. The study contributes to a deeper understanding of the relationship between embodied experience and reflective processes in the context of Embodied and Aesthetic Education. It offers starting points for the discussion of didactic consequences concerning promoting embodied reflexivity. It points out the meaningfulness of embodied/somatic practices in teacher education, as fostering an embodied self-perception could be a valuable approach to enhancing self-reflection.